Endocannabinoid modulation of nociceptive processing - Norris, Leonie (2010)
The analgesic effects of cannabis-based medicines are widely described and elevation of the endocannabinoids (ECLs), by inhibition of endocannabinoid metabolism, also produces analgesia. Measurement of endocannabinoids (ECLs) and metabolites, in low weight biological tissue, provides an important tool for investigating the potential therapeutic effects of this receptor system.